Graphics Programming Solutions / For IBM PCs and Compatibles - VGA, SuperVGA, and XGA - Real-Time Animation - Bit-Mapped Graphics - Canton P. Maria; Sanchez Julio (Mcgraw Hill, Inc, 1993)
The fundamental tools required for developing quality, high-resolution graphics applications on VGA, XGA, and Super VGA systems. Introduction to Microcomputer Graphics, VGA Architecture, VGA Device Drivers, VGA Setup and Text and Bitmap Primitives, VGA Geometrical Primitives, The XGA and 8514/A Adapter Interface, XGA Architecture and Programming, Super VGA Programming, Animation, Bit-Mapped Graphics, Programming Graphics Hardcopy Devices, Installing the Software, Using the Library Software, IBM BIOS Data and Video Services, Bibliography, Index.